Safety Profile of Oxaliplatin in 3,687 Patients With Cancer in China: A Post-Marketing Surveillance Study - Yu, Zaoqin; Huang, Rui; Zhao, Li; Wang, Ximin; Shangguan, Xiaofang; Li, Wei; Li, Min; Yin, Xianguo; Zhang, Chengliang; Liu, Dong (Frontiers in Oncology, 2021)
Background: Oxaliplatin (OXA), a third-generation platinum derivative, has become one of the main chemotherapeutic drugs for colorectal cancer and other cancers, but reports of adverse reactions are also increasing with the extensive application of OXA. In this study, post-marketing surveillance was carried out to investigate the safety profile of OXA in a real-world setting in Chinese cancer patients to provide a reference for the rational application of OXA. Methods: All patients with cancer who received OXA-based chemotherapy in 10 tertiary hospitals in Hubei Province, China, between May 2016 and November 2016 were enrolled. A central registration method was used to document patients’ demographics, clinical use, and any incidence of adverse reactions to OXA. All adverse drug reactions (ADRs) were collected and analyzed to assess causality, severity, treatment, and outcome. Results: In total, 3687 patients were enrolled in this study. Approximately 64.6% of the patients were male, and 68.8% were aged 50-70 years, with a mean age of 55.3 years. The proportions of patients diagnosed with colorectal and gastric cancers were 59.3% and 31.6%, respectively. In this study, the overall incidence of ADRs and serious ADRs was 42.7% and 1.3%, respectively. The most common ADRs were gastrointestinal disorders (25.7%), blood disorders (21.1%), and peripheral nervous system disorders (8.0%). The serious ADRs identified were hypersensitivity reactions, thrombocytopenia, abnormal hepatic function, and leukopenia/neutropenia. The median onset of gastrointestinal toxicity, myelosuppression, peripheral neurotoxicity, and abnormal hepatic function was 1 d, 5 d, 1 d, and 14 d, respectively. The majority (84.7%) of hypersensitivity reactions were mild to moderate, and the median time to onset of these reactions was within the first 20 min of OXA infusion. Almost 88.0% of patients who experienced ADRs recovered or improved with treatment. Conclusion: Our data suggest that OXA-induced ADRs are very common in Chinese patients with cancer; however, more attention should be paid to hypersensitivity reactions caused by OXA. This study provides a valuable reference regarding the safe application of OXA in a real-world setting.